Analisis Pembelajaran Daring Pendidikan Jasmani Olahraga dan Kesehatan Bagi Siswa Berkebutuhan Khusus di SLB Tunas Harapan Karawang - Rimanto (Universitas Singaperbangsa, 2022)
This research uses descriptive qualitative research. This is because the data that will be obtained from this study are in the form of words, not numbers, while the dependent variable is learning physical education, sports and health. The object of this research is the analysis of online learning difficulties in physical education, sports and health for students with special needs at SLB Rajawali Makassar. receive information clearly, quadriplegic has the characteristics of having one limb that is not perfect, autism is individualistic or has a life of its own, down syndrome children tend to have a high level of self- confidence. The population and sample in this study were 4 students from each disability. Research data obtained by using a questionnaire or questionnaire and interviews. The analytical technique used in this study is a descriptive analysis technique in the form of words. Based on the results of the research conducted, it was concluded that in terms of providing material for children with special needs, it was difficult to select and provide suitable material for children with special needs and require special corner books for children with special needs, difficulties in online learning practices for corner subjects 1) facilities and infrastructure that are not owned by students, 2) Teacher's role in modifying learning tools and techniques, 3) Lack of time for parents in online learning assistance, 4) Poor network.